Effect of Ru Interlayer thickness on Electrophysical Properties of Co/Ru/Co three-layer film systems - Lohvynov, A.M.; Cheshko, I.V.; Pazukha, I.M.; Tyschenko, K.V.; Pylypenko , O.V.; Zahorulko , A.Yu. (Physics and Chemistry of Solid State, 2022)
In this paper, the investigation of the crystal structure and electrophysical properties of Co/Ru/Co/Sub three-layer film systems with a Ru layer thickness dRu = 5-20 nm has been carried out. It is shown that for both as-deposited and annealed at 800 K thin-film samples the phase composition corresponds to hcp-Co + hcp-Ru. The dependence of resistivity and temperature coefficient of resistance as a function of dRu was received. It was demonstrated that the change in the resistivity value during the first cycle of heat treatment stays more significant than more Ru layer thickness. The value of temperature coefficient of resistance has an order of 10-4 and growth from 5.05×10-4 to 6.42×10-4 K-1 within the dRu range 0-20 nm.